MODELING OF UNDERGROUND STRUCTURES SUBJECTED TO EARTHQUAKE BY COMBINING 1D FREE-FIELD AND 2D PSEUDO-STATIC ANALYSES - Tereza Poklopová; Veronika Pavelcová; Tomáš Janda; Michal Šejnoha (Acta Polytechnica CTU Proceedings)
The paper deals with the evaluation of tunnel construction subjected to earthquake using a pseudostatic analysis combined with the finite element method. The initial stage of calculation is concerned with the design of computational model and subsequent analysis of the actual excavation process. The case study of the response of a selected construction to earthquake follows next. To that end, the so called 1D free filed dynamic analysis is performed first to generate appropriate loading conditions in terms of a layered-wise constant shear strain. Therein, two particular boundary conditions, termed the fixed and absorbing boundary, are examined. The corresponding loading conditions are finally introduced in a 2D plane strain analysis to yield the internal forces developed in the tunnel lining. The results clearly show inadequacy of the fixed boundary and promote the use of absorbing boundary conditions for the present soil profile.